Shocking Escape: A Cardiac Escape Room for Undergraduate Nursing Students. (February 2021) - Morrell, Briyana; Eukel, Heidi N
Background: Cardiovascular content is challenging for students to master in the undergraduate nursing curriculum.Educational escape rooms have been shown to be useful in increasing student knowledge, immersing students in the learning process, and facilitating the growth of soft skills among learners. Aim: This article details acardiovascular educational escape room in an undergraduatenursing course, including educational objectives, design considerations, and all materials for seamless transferability into other curricula. Methods: Faculty designed, implemented, evaluated, and revised anursing cardiovascular escape room over three years. In this sequential-style escape room, junior-level students worked together in groups to complete nine puzzles and activities. The student teams solved puzzles during the allotted 60 minutes to save a fictional patient at risk for further clinical deterioration related to cardiogenic shock. Participants complete activities including drug dosage calculations, rebus puzzles, multiple choice items, and clinical reasoning activities based around course and licensing objectives for the content area in nursing education. Upon game conclusion, faculty lead a guided debriefing to close the loop of learning. The escape room has been implemented for groups ranging from 31 to 68 students in each cohort. Results: Previously published results on this topic indicate that student content knowledge improved after the event. Students also reflected growth in confidence, critical thinking, and teamwork and also appreciated the real-life nature of the activity. The educational game can be adapted and transferred to other schools of nursing or clinical sites.